Identification of intrinsic catalytic activity for electrochemical reduction of water molecules to generate hydrogen. Issue 23 (21st June 2015) - Shinagawa, Tatsuya; Takanabe, Kazuhiro
<x xml:space="preserve">Abstract</x> Addition of foreign metal onto platinum nearly doubles its reactivity toward water molecule reduction under unbuffered neutral pH conditions.